Documentary analysis of Ukraine's educational policy in the context of conflict: the case of the ban on training lawyers in law enforcement agencies - Степаненко, Оксана Василівна; Степаненко, О. В.; Stepanenko, Oksana V.; Степаненко, Андрій Сергійович; Степаненко, А. С.; Stepanenko, Andrii S.; Костенко, Сергій Костянтинович; Костенко, С. К.; Kostenko, Sergiy K.; Колодін, Денис Олексійович; Колодін, Д. О.; Kolodin, Denys O.; et al. (Naguanagua : Universidad de Carabobo, 2025)
This article provides a documentary overview of the main regulatory and institutional changes that have characterized higher education policy in Ukraine in recent years, particularly in the context of the ongoing armed conflict and systemic reforms. Based on an analysis of laws, government decrees, strategic documents and ministerial guidelines, the study identifies key priorities such as the digitization of learning, strengthening university autonomy, internationalization efforts, modernizing education management and institutional resilience. Particular attention is paid to the ban on the training of lawyers in law enforcement and military higher education institutions, which is a typical example of the conceptual changes taking place in Ukrainian higher education. This political decision is seen in the context of efforts to harmonize legal education with European standards, increase academic transparency and consolidate legal training in civilian institutions. The aim of this article is to provide a thematic overview of recent policy changes from a normative and propositional perspective, without conducting an evaluative analysis of individual academic programs or professional training outcomes. By focusing on both general trends and the specific case of legal education reform, the study contributes to a better understanding of how conflicting transformations intersect with long-term policy goals in Ukraine's higher education system.
Kolodin D. Documentary analysis of Ukraine's educational policy in the context of conflict: the case of the ban on training lawyers in law enforcement agencies / O. Stepanenko, A. Stepanenko, S. Kostenko et al. // Eduweb-Revista de Tecnologia de Informacion y Comunicacion en Educacion. – Naguanagua : Universidad de Carabobo, 2025. – 19(2). - P. 252-265. URL: https://doi.org/10.46502/issn.1856-7576/2025.19.02.17
Keywords: higher education in Ukraine; educational policy; legal education; higher education reform; academic independence; educational standards